EFECTIVENESS OF PLATELET-RICH PLASMA IN OSTEOARTHRITIS OF THE KNEE JOINT - Basuki Supartono; T, Rarasati; S, Wiyono; Y, Suciati (BMJ Publishing Group Limited, 2016)
Backgound The clinical evidence of Platelet-Rich Plasma (PRP) is still insufficient. The aim of this research is to compare the efficacy of hyaluronic (HA) and HA-PRP injection on osteoarthritis (OA) of the knee joint. Material and methods A cross-sectional study using 58 patients medical record of Al Fauzan Hospital, Jakarta Indonesia. 27 patients received HA injections, and 31 patients received HA-PRP injections. Patients were evaluated using IKDC and WOMAC score until 2 months after injections. The data were analysing with Shapiro Wilk, Paired t, Wilcoxon, Mann Whitney, Kruskal Wallis and Post Hoc test.